2013
DOI: 10.5897/ajb12.622
|View full text |Cite
|
Sign up to set email alerts
|

Effect on some haematological indices of human whole blood when aqueous leaf extract of Euphorbia heterophylla was used as storage anticoagulant

Abstract: Properties of red blood cells, especially cell size and red cell indices related to size, change with time in stored blood samples. Laboratory anticoagulants have certain drawbacks. For example, heparin has no preservative property on whole blood while K 3 EDTA (EDTA) is toxic and damages platelets. The search for novel anticoagulants with better hematological profile is therefore necessary. The anticoagulant properties of aqueous leaf extract of Euphorbia heterophylla (aka ito in Igbo) were compared with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In severe cases, it could also present as thrombocytosis, and may cause organ damage due to blood clot in organs. However, Ugachukwu et al (32) reported that the aqueous leaf extract of E. heterophylla had a good anticoagulant effect on human whole blood. The nonsignificant differences of WBC, lymphocytes, granulocytes, and mid cells suggest that the plant extract had no toxic effects on the immune system in the subacute and subchronic toxicity studies.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, it could also present as thrombocytosis, and may cause organ damage due to blood clot in organs. However, Ugachukwu et al (32) reported that the aqueous leaf extract of E. heterophylla had a good anticoagulant effect on human whole blood. The nonsignificant differences of WBC, lymphocytes, granulocytes, and mid cells suggest that the plant extract had no toxic effects on the immune system in the subacute and subchronic toxicity studies.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in haemoglobin (MCH and MCHC) causes oxygen transport to the tissues. An increase or decrease in blood attributes might be owed to free radical scavenging activity of extract, anticoagulation by extract [41]; antiuglycosylation [64]; thrombolytic potential [42] or by genotoxicity [65]. The practical application of the plant secondary metabolites should be based upon their careful and extensive study regarding medicinal and toxicological nature.…”
Section: Discussionmentioning
confidence: 99%
“…The Ethanol used was of high purity. Human blood from a healthy volunteer was utilized for in vitro assessment of haemotological indices [41][42]. Means of three replicates for each sample were used to reduce the error for comparison with normal blood characteristics.…”
Section: Experimental Planmentioning
confidence: 99%
“…It was also observed that oral administration of aqueous leaf extract of the plant significantly reduced plasma glucose concentration of experimental induced diabetes in rats [9]. Aqueous leaf extract of E. heterophylla has also been reported to have good anticoagulant and preservative effect on human whole blood [10].…”
Section: Introductionmentioning
confidence: 99%